David Sackett on the move; Paul Glasziou takes over. Issue 3 (1st June 1999) - Haynes, Brian
Abstract : This issue of Evidence-Based Medicine marks a change of co-editor, David Sackett, one of the founding editors of Evidence-Based Medicine, has resigned this postto begin his next career. Paul Glasziou has taken Sackett's place as co-editor.